2015
DOI: 10.1177/0733464815591211
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Perceptions of Fall Detection Devices

Abstract: A third of adults over the age of 65 are estimated to fall at least once a year. Perhaps as dangerous as the fall itself is the time spent after a fall if the person is unable to move. Although there are many devices available to detect when a person has fallen, little is known about the opinions of older adults regarding these fall detection devices (FDDs). We conducted five focus groups with 27 older adults. Transcripts from sessions were coded to generate themes that captured participants' perceptions. Them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…Wearable sensors as part of a falls prevention alarm system can provide new opportunities for individualized monitoring of patients [ 20 22 ] where human motion data can be collected and transmitted in real time for analysis. More importantly, recent studies [ 23 , 24 ] suggest that older people have demonstrated interest in small sensors embedded in their clothing. In addition, as sensors are decreasing in size and power consumption, the inclusion of multiple sensors can further extract physiological signals of interest [ 20 22 ] along with motion data.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable sensors as part of a falls prevention alarm system can provide new opportunities for individualized monitoring of patients [ 20 22 ] where human motion data can be collected and transmitted in real time for analysis. More importantly, recent studies [ 23 , 24 ] suggest that older people have demonstrated interest in small sensors embedded in their clothing. In addition, as sensors are decreasing in size and power consumption, the inclusion of multiple sensors can further extract physiological signals of interest [ 20 22 ] along with motion data.…”
Section: Introductionmentioning
confidence: 99%
“…Potencjalne korzyści technologii detekcji aktywności ruchowej w domu dla utrzymania zdrowia i niezależności osób starszych (jak również opinie osób starszych związanych z użytkowaniem takich systemów) są przedmiotem badań ostatnich lat [6,7,8,9,10,11,12]. W związku ze zdalnym monitorowaniem w doniesieniach rozpatruje się określenie potrzeb i oczekiwań seniorów oraz członków ich rodzin [13].…”
Section: Zdalne Monitoring Osób Starszych -Problemyunclassified
“…A variety of FDDs, including the one using a hearing aid with an embedded inertial sensor, have been previously used in research (Lindemann et al 22 ; Bourke et al 7 ). Common wearable FDDs include neck-worn pendants, smartphone apps, and wrist-worn devices (Aguiar et al 2 ; Lipsitz et al 23 ; Chaudhuri et al 8 ). Others have used environmental sensors such as cameras or microphones to detect falls in fixed locations, for example, in the laboratory, within nursing facilities (Rougier et al 31 ; Li et al 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…One possible solution to increase fall-detection-monitoring technology adoption may be to integrate FDDs into functional hearing instruments, which are less-conspicuous than other forms of FDDs, are commonly already being worn by individuals who are at risk for falling, and have become progressively less-stigmatized, wearable devices (Rauterkus and Palmer 28 ; Chaudhuri et al 8 ).…”
Section: Introductionmentioning
confidence: 99%